Hydration modulates oxygen channel residues for oxygenation of cysteine dioxygenase: Perspectives from molecular dynamics simulations - ÖZBEK SARICA, PEMRA (ELSEVIER SCIENCE INC, 2022)
Cysteine dioxygenase (CDO) regulates the concentration of L-cysteine substrate by its oxidation in the body to prevent different diseases, including neurodegenerative and autoimmune diseases. CDO catalyzes the oxidation of thiol group of L-cysteine to L-cysteine sulfinic acid using molecular oxygen. In this study, molecular dynamics simulations were applied to ligand-free CDO, cysteine-bound CDO, and oxygen-bound CDO-cysteine complex which were primarily subjected to the evaluation of their structural and dynamical properties. The simulation data provided significant information not only on the conformational changes of the enzyme after its ligation but also on the co-ligation by sequential binding of L-cysteine and molecular oxygen. It was found that the ligation and co-ligation perturbed the active site region as well as the overall protein dynamics which were analyzed in terms of root mean square deviation, root mean square fluctuation and dynamic cross correlation matrices as well as principal component analysis. Furthermore, oxygen transport pathways were successfully explored by taking various tunnel clusters into account and one of those clusters was given preference based on the throughput value. The bottleneck formed by different amino acid residues was examined to figure out their role in the oxygenation process of the enzyme. The residues forming the tunnel's bottleneck and their dynamics mediated by water molecules were further investigated using radial distribution functions which gave insights into the hydration behavior of these residues. The findings based on the hydration behavior in turn served to explore the water-mediated dynamics of these residues in the modulation of the pathway, including tunnel gating for the oxygen entry and diffusion to the active site, which is essential for the CDO's catalytic function.
Keywords: Cysteine dioxygenase; Molecular dynamics simulations; Oxygen tunnels; TISSUE-SPECIFIC EXPRESSION; STRUCTURAL ORGANIZATION; PROTEASOME SYSTEM; FORCE-FIELD; CROSS-LINK; MECHANISM; INSIGHTS; IDENTIFICATION; DEGRADATION; PARAMETERS